(untitled) (Proceedings of International Educators Conference, 2024)
This article explores the pivotal role played by international organizations in shaping global governance. Through a comprehensive literature analysis, we examine the evolution of international organizations, their functions, and their impact on addressing global challenges. The methods section delves into the mechanisms through which these organizations operate, while the results section highlights their achievements and limitations. The discussion section critically assesses their effectiveness, considering diverse perspectives. Finally, conclusions are drawn, and suggestions are proposed for enhancing the role of international organizations in fostering a more sustainable and equitable world.